Pengembangan Alat Peraga Braille Berbasis IoT untuk Meningkatkan Akses dan Kemandirian Belajar Mahasiswa Tunanetra PGSD - Erwin Nurdiansyah; Ince Prabu Setiawan Bakar; Supriadi Supriadi; Kamal Kamal; Nurul Ilmi Hairullah; Arif Hukmi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
Access to appropriate learning media for blind students in higher education remains limited, particularly in the area of Braille literacy. This situation highlights the urgent need for assistive technology that enables students to learn independently and engage actively in the learning process. This study aims to develop an Internet of Things (IoT)–based Braille letter recognition teaching aid to support accessibility and learning autonomy for blind students, especially those in the Primary School Teacher Education (PGSD) Study Program at Universitas Islam Makassar. The development procedure includes user needs analysis, system and hardware design, as well as device prototyping using an Arduino Mega microcontroller integrated with an MP3 shield for audio guidance and solenoid actuators for Braille output. The results show that the device provides interactive learning experiences through voice instructions and accurate tactile Braille patterns that users can recognize independently. The integration of IoT technology also enables remote access, reducing dependence on classroom-based learning and expanding learning opportunities. These findings indicate that IoT-based assistive tools can contribute significantly to building inclusive learning environments in higher education. The study recommends continued collaboration between academic programs and Disability Service Units to refine the device and enhance its adaptability to users’ needs.